Beyond band of brothers - Winters, Richard D.; Kingseed, Cole C. (Cole Christian), 1949- (New York : Berkley Caliber, 2006)
They were called Easy Company, but their mission was never easy. Immortalized as the Band of Brothers, they suffered 150% casualties while liberating Europe, an unparalleled record of bravery under fire. Dick Winters was their commander, and this is his story based on his wartime diary. Only Winters was present from the activation of Easy Company until the war's end. On D-Day, Dick Winters parachuted into France and assumed leadership of the company when their commander was killed. He led them through the Battle of the Bulge and into Germany, where they liberated an S.S. death camp from the horrors of the Holocaust and captured Berchtesgaden, Hitler's alpine retreat. After briefly serving during the Korean War, Winters was a highly successful businessman.--From publisher description.
I: Bank of Brothers -- Beginnings -- There is nothing easy in easy company -- From Benning to Shanks -- Old beyond my years -- II: In the time of achilles -- Day of days -- Carentan -- Holland -- The island -- III: In war's dark crucible -- Interlude -- Surronded again -- The final patrols -- Victory -- IV: Finding peace after a lifetime of war -- Occupation -- Coming home -- Steve Ambrose slept here -- Reflections.
Keywords: Winters, Richard D; United States. -- Army. -- Parachute Infantry Regiment, 506th. -- Company E -- History; World War, 1939-1945 -- Personal narratives, American; World War, 1939-1945 -- Campaigns -- Western Front; World War, 1939-1945 -- Aerial operations, American; United States. -- Army -- Biography; Soldiers -- United States -- Biography